LATAR BELAKANG PENYEBAB ANAK PUTUS SEKOLAH DI DESA KOTOTUO KECAMATAN XIII KOTO KAMPAR PROVINSI RIAU - Liza Novita Sari; Swiss Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study was conducted at Desa Kototuo Kecamatan XIII Koto Kampar Provinsi Riau. The study was titled "Background Cause of Children Drop Out at Desa Kototuo Kecamatan XIII Koto Kampar Provinsi Riau. The purpose of this study was to determine the background of the causes of children dropping out of school at Desa Kototuo Kecamatan XIII Koto Kampar Provinsi Riau. The focus of this research is the factors that influence the interest of the child to education at Desa Kototuo Kecamatan XIII Koto Kampar Provinsi Riau. The subjects studied were junior high school dropouts at Desa Kototuo Kecamatan XIII Koto Kampar As many as five research subjects. The author uses descriptive and qualitative methods of data are analyzed qualitatively and using purposive sampling technique. Data instruments are observations, in-depth interviews and documentation. Research conducted at Desa Kototuo Kecamatan XIII Koto Kampar On the background of the causes of dropping out of school at Desa Kototuo Has been done. A study of five school dropouts and their parents found that the underlying causes of dropouts consisted of a parent background, an environmental background, and an economic background. The research found that the causes of drop out in school Desa Kototuo Due to the low interest of the child to education. The low interest of the child to this education is influenced by, parents' interest in education, parental concern for education and parental involvement in education. Keywords: Education, Disconnect, Factors